Management Of Mosque Infaq Funds In Improving The Welfare Of Micro And Small Businesses From The Perspective Of Islamic Law - Masykuroh, Yufi Wiyos Rini; Kurniati, Herlina; Septiana, Evi (Universitas Islam Negeri Raden Intan Lampung, 2024)
The mosque has a function not only as a place of mahdhoh worship but also as a center for Muslim socio-economic activities (social economy center), namely through infaq, and alms productively, as happened at the Nurul Hidayah mosque in Panjang Utara village, one of the programs carried out is to improve the welfare of small micro businesses around the mosque environment. The purpose of this study is to determine and analyze in Islamic law the practice of managing infaq and alms funds in improving the welfare of small micro businesses at the Nurul Hidayah Mosque in Panjang Utara. The method used in this research is qualitative with descriptive method, the object of research is the amil zakat institution, infaq and alms of the Nurul Hidayah Mosque. The data sources used are primary and secondary data sources. The collection techniques are interviews and documentation. Based on the results of the study, it can be concluded that the management of the infaq funds of the Nurul Hidayah Mosque in improving the welfare of small micro businesses by providing loans without any administrative costs, guarantees and interest or margins, this is done so that it is beneficial to customers not only in the short term but more than that, namely in the long term, while the perspective of Islamic law on the management of infaq and alms funds in improving the welfare of small and medium micro businesses at the Nurul Hidayah Mosque in Panjang Utara village is in accordance with Islamic law, but in the future the distribution of infaq and alms should be further expanded to other groups.Keywords: Ibadah Mahdhoh; Micro Small and Medium Enterprises; Management of Infak Funds